Planning, access to water and HIV/AIDS driven health challenges in Ivory Park, ward 77 - Siphumeze, Mndze (My University, 2010)
Apartheid planning led to the unequal distribution of social services in South African communities. This happened since apartheid planning delivered social services on the basis of colour. In this process, the white communities got proper delivery of social services while the black communities got very limited or no delivery of social services. In doing this, the apartheid planning hindered access to water in many areas of South Africa (S.A) especially in informal settlements such as those of Ivory Park, Soweto and Alexandra. Blacks who tend to be unemployed with very low levels of education, training and skills dominate these areas. Constitutionally, black people are made up of Africans, Coloureds and Indians. In addition, blacks who reside in informal settlements tend to be poverty stricken. The lack of reliable access to water in Ivory Park, ward 77 which is the focus of this report is accompanied by high rate of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) that comes with health challenges. The HIV/AIDS driven health challenges are manifested by excessive periods of diarrhoea, repeated release of faeces, HIV/AIDS infected body fluids including urine that contaminate the beds, linen and clothes of the HIV/AIDS patients to mention just few examples. In the initiative that aims to respond to the HIV/AIDS driven health challenges, the communities formed HIV/AIDS based care giving institutions which are normally run by the HIV/AIDS based caregivers. The HIV/AIDS based care giving institutions counter HIV/AIDS driven health challenges by the use of water. That means, without access to water, the HIV/AIDS based care giving cannot be undertaken in an effective manner. Ivory Park, ward 77 has poor access to water, and the informal settlement has a high rate of HIV/AIDS. This report shows the role that can be played by access to water in dealing with health challenges that are driven by HIV/AIDS in Ivory Park, ward 77. It does that by revealing the challenges of access to water and the correlation between water and HIV/AIDS. In showing the role of water in dealing with HIV/AIDS driven challenges, this research report acknowledges that water cannot cure HIV/AIDS. It also accepts the fact that the Antiretroviral drugs, nutritious food and proper medical care should accompany access to water to provide a comprehensive care and support to the HIV/AIDS patients. This research report dwells on access to water in the context of dealing with health challenges that are posed by the epidemic. It strongly contends that quantity and quality of water are of paramount importance in the efforts that aim at providing an effective HIV/AIDS based care giving. In arguing on access to water and HIV/AIDS based care giving, the Communicative Theory which calls for a dialogue guides the facts and issues that are documented in this report. In applying the Communicative Theory, this report argues that HIV/AIDS based caregivers should be included in the decision making that has to do with planning the delivery of water. This is done with the application of the perspectives that are borrowed from Advocacy Theory.